PERAN MULTIMEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN KETERAMPILAN MENULIS MURID SEKOLAH DASAR: STUDI PUSTAKA - Minda Permei Sela; Dian Indihadi; Dwi Alia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the role of interactive learning multimedia in supporting Indonesian language writing skills in elementary school students based on a synthesis of relevant literature. Data were obtained from national journal articles published between 2022 and 2025 and relevant to the use of interactive multimedia in writing learning. Analysis was conducted through reading, categorizing, comparing, and synthesizing research findings to obtain a comprehensive conceptual overview. The study results indicate that interactive learning multimedia contributes to increasing student engagement, motivation, and the ability to develop ideas, construct sentences, and organize writing systematically. Furthermore, interactive multimedia supports more concrete, engaging, and student-centered learning through the integration of text, images, audio, and animation. These findings demonstrate that interactive learning multimedia has the potential as an innovative medium to support the improvement of elementary school students' writing skills, based on the literature reviewed. These findings are expected to form the basis for developing technology-based learning strategies that are effective, relevant, and appropriate to the 21st-century literacy needs of elementary school students.